Chemotaxonomy of South Indian Piper - BABU, P N RAVINDRAN, K NIRMAL (Journal of Spices and Aromatic Crops, 1994)
A chemotaxonomical study was carried out on South Indian taxa of Piper to understand their interrelationships. Fourteen taxa were analysed for their flavonoids and based on presence or absence ofthese compounds, percentage similarity indices were calculated. The results in general supported the species delimitation and taxonomical relationships arrived at by conventional taxonomy using morphological characters. A chemical dichotomy was evident between the two sub genera - Pipali (having erect spikes) and Maricha (having pendant spikes) thereby supporting the validity of the sectional classification.